DEVELOPING A WEB-BASED INFORMATION SYSTEM IN DETECTION OF HIGH-RISK PREGNANCIES IN SEMARANG, INDONESIA: ADDIE MODEL - Ihsanti Indri Fajriya; Supriyana Supriyana; Bahiyatun Bahiyatun; Melyana Nurul Widyawati (Belitung Nursing Journal, 2017)
A web-based information system in this study was developed using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instruction model to facilitate the monitoring and reporting the existence of high-risk pregnancies in Semarang. The evaluation of the system revealed that web-based information system was very effective in terms of completeness, ease, timeliness, accuracy, and conformity with p-value <0.05. This innovation is expected to contribute positively to reduce maternal mortality rates in Indonesia, especially in Semarang.